Potret Kemiskinan dalam Cerpen Senyum Karyamin Karya Ahmad Tohari: Kajian Sosiologi Sastra - Neli Husna Erwin; Abdurahman Abdurahman (Indo Publishing, 2026)
This study aims to describe the portrayal of poverty in Ahmad Tohari’s short story “Senyum Karyamin” through a sociological approach to literature. This short story was selected because it depicts the lives of the lower class, which are fraught with social and economic problems, and reflects the realities of life closely tied to the conditions of marginalized communities. The method used in this study is qualitative descriptive analysis employing content analysis techniques. Data was obtained from the short story text, which was analyzed based on social aspects that deeply reflect conditions of poverty. The research findings indicate that the poverty experienced by the character Karyamin is not merely economic in nature, but is also influenced by an unjust social structure that fails to support the underprivileged. This is evident in the character’s inability to meet basic needs, harsh working conditions, and pressures from the economic system such as the presence of middlemen, debt, and burdensome social obligations. Furthermore, a strong social irony is present: the character, who is starving, is asked to contribute to a humanitarian fund. The short story also portrays individual resilience through the symbol of a “smile,” which reflects both resignation and the struggle to survive in the face of life’s harsh realities. Thus, this short story not only depicts the reality of poverty but also offers a social critique of economic inequality and the lack of social awareness in society. This study is expected to provide a deeper understanding of the relationship between literary works and social reality, particularly in examining the living conditions of the lower class.